How to Support Parents of Infants and Young Children in Mental Health Care: A Narrative Review - Stolper, Hanna; van Doesum, Karin; Steketee, Majone (Frontiers in Psychology, 2021)
Objective: The aim of this narrative review is to gain insight into the appropriate intervention targets when parents of infants and young children suffer from psychopathology. Background: Psychopathology in parents is a risk factor for maladaptive parenting and is strongly related to negative cascade effects on parent-child interactions and relations in the short and long term. Children in their first years of life are especially at risk. However, in adult mental health care, this knowledge is rarely translated into practice, which is a missed opportunity for prevention. Methods: Electronic databases were searched for reviews. In addition, sources were obtained via manual search, reference mining, expert opinion, and communications from conferences. In total, 23 reviews and 11 meta-analyses were included. Results: Findings regarding targets of intervention were identified in different interacting domains, namely the parental, family, child, and environmental domains as well as the developing parent-child relationship. A “one size fits all” intervention is not appropriate. A flexible, tailored, resource-oriented intervention program, multi-faceted in addressing all modifiable risk factors and using different methods (individual, dyadic, group), seems to provide the best results. Conclusion: To address the risk factors in different domains, adult and child mental health care providers should work together in close collaboration to treat the whole family including mental disorders, relational, and contextual problems. A multi-agency approach that includes social services is needed.